Physicochemical Characterization of Ethanol Organosolv Lignin (Eol) from Eucalyptus Globulus: Effect of Extraction Conditions on the Molecular Structure - Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Yanez-Sanchez, M (Elsevier Ltd, 2014)
The aim of the present study was to investigate the effect of extraction conditions, mainly severity factor (H-factor = 3980-14,500) on the molecular structure of ethanol organosolv lignins extracted from Eucalyptus globulus. Isolated lignins were structurally characterized by 1H NMR, 31P NMR, UV-Vis, FT-IR spectroscopy and gel permeation chromatography. The results showed that an increase in the severity of the pretreatment decreased the molecular weight of the lignins within a 36-56% range with respect to the untreated lignin (MWL). Moreover, the increase in severity of the organosolv treatment was accompanied by strong decrease in the content of aliphatic hydroxyl groups and by an increase of syringyl phenolic units and condensed phenolic structures. The condensed phenolic structures quantified in the organosolv lignin correspond to resinol, phenylcoumaran, dibenzodioxocin, spirodienone and ?-1? linkages. © 2014 Elsevier Ltd. All rights reserved.